Street Prostitution Zones and Crime - Paul Bisschop; Stephen Kastoryano; Bas van der Klaauw (Institute for the Study of Labor (IZA), 2015)
This paper studies the effects of introducing legal street prostitution zones on both registered and perceived crime. We exploit a unique setting in the Netherlands where legal street prostitution zones were opened in nine cities under different regulation systems. We provide evidence that the opening of these zones was not in response to changes in crime. Our difference-in-difference analysis using data on the largest 25 Dutch cities between 1994 and 2011 shows that opening a legal street prostitution zone decreases registered sexual abuse and rape by about 30% to 40% in the first two years. For cities which opened a legal street prostitution zone with a licensing system we also find significant reductions in drug-related crime and long-term effects on sexual assaults. Perceived drug nuisance increases upon opening but then decreases below pre-opening levels in cities with a licensed prostitution zone. In contrast, we find permanent increases in perceived drug crime in the areas adjacent to the legal prostitution zones.
Keywords: J16; J47; K14; K23; K42; 330; prostitution; registered crime; perceived crime; regulation; difference-in-difference